Theoretical evaluations of self-absorption correction factors / Ahmad Saat - Saat, Ahmad (Universiti Teknologi MARA Cawangan Pahang, 2000)
The note describes how self-absorption of gamma-rays in gamma-ray spectrometry can be evaluated mathematically. It was shown that the correction factor depends on the mean absorption path length of gamma-rays in the particular sample. An experimental procedure to determine self absorption correction factors of any sample-detector geometries is also briefly described.